IMPACT OF THE NORDIC HAMSTRING AND HIP EXTENSION EXERCISES ON HAMSTRING ARCHITECTURE AND MORPHOLOGY: IMPLICATIONS FOR INJURY PREVENTION. Issue 4 (1st February 2017) - Bourne, Matthew; Duhig, Steven; Timmins, Ryan; Opar, David; Williams, Morgan; Kerr, Graham; Shield, Anthony
Abstract : Background: There has been significant interest in exploring the patterns of muscle activity in hamstring exercises, however, there is no research examining the architectural and morphological adaptations of these muscles to different exercise interventions. Objective: To evaluate changes in biceps femoris long head (BFLH ) fascicle length and hamstring muscle size following Nordic hamstring exercise (NHE) or hip extension (HE) training. Design: In this longitudinal study, participants were randomly allocated to one of three groups: 1) HE training (n=10), NHE training (n=10), or no training (CON) (n=10). BFLH fascicle length was assessed before, during (Week 5) and after the intervention with 2D-ultrasound. Hamstring muscle size was determined before and after training via magnetic resonance imaging. Setting: Laboratory based. Patients (or Participants): Thirty recreationally active males (age, 22.0±3.6 years, height, 180.4±7 cm, weight, 80.8±11.1 kg). Intervention: A 10-week progressive intensity strength program consisting exclusively of NHE, HE training, or a period of no training. Main Outcome Measurements: BFLH fascicle length and hamstring muscle volumes. Results: Compared to baseline, BFLH fascicles were lengthened in the HE and NHE groups at mid- ( d= 1.12–1.39, p<0.001) and post-training ( d= 1.77–2.17, p<0.001) with no difference observed between training groups ( d= 0.49–0.80, p=0.279–0.976). BFLH volume increased more for the HE than the NHE ( d= 1.03, p=0.037) and CON ( d= 2.24, p<0.001) groups. Compared to the CON group, both exercises induced significant increases in semitendinosus volume ( d= 2.16–2.50, ≤0.002) which were not significantly different ( d= 0.69, p=0.239). Conclusions: NHE and HE training both stimulate significant increases in BFLH fascicle length, however, HE training may be more effective for promoting hypertrophy in the BFLH .